AN INVESTIGATION OF THE EFFECTIVENESS OF FIELD TRIPS ON ACADEMIC ACHIEVEMENT OF BASIC SCIENCE STUDENTS IN LAGOS STATE - Timothy, James; Apata, F. S. (Sokoto Educational Review, 2014)
This study investigated the effectiveness of field trips on the academic performance of basic science students in Lagos State. A total of four research questions and four null hypotheses were formulated and tested at 0.05 level of significance. The population comprised of all the basic science students in all the twenty public junior secondary schools in Surulere Local Government Area of Lagos State out of which two co-educational schools were randomly selected using the balloting system. The research design was a pre-test, post-test experimental control group design. There were two research instruments. These were the Achievement Test in Basic Science (ATBS) and Attitudinal Questionnaire in Basic Science (AOBS). The data collected from the study were processed and analyzed using frequency counts and percentages while the four hypotheses were analyzed using Analysis o f covariance (ANCOVA). The result of the hypotheses revealed that field trip strategy was found to be more effective in improving the academic achievement of, basic science students. It was therefore recommended that field trip strategy o f teaching should be emphasized and collaborated with other methods o f teaching science.